Synthesis and antimicrobial activity of 1,3-bis-butyl-5-(4-iodophenyl)-1,3,5-triazacyclohexane - Lefrada, Leila; Köhn, Randolf; Malki, Souhila; Mazouz, Wissam; Bouchemma, Ahcene; Hadjem, Meriem (European Journal of Chemistry, 2017)
This work describes the synthesis, structural characterization and antibacterial activities of 1,3,5-triazacyclohexane type of new compound 1,3-bis-butyl-5-(4-iodophenyl)-1,3,5-triazacyclohexane. The new triazacyclohexanes (R3TAC) with mixed aryl and alkyl N-substituents are synthesized by the reaction of a 1:2 mixture of 4-iodoaniline and n-butylamine with formalin. The synthesized compounds were characterized by spectral analysis IR, 1H NMR and 13C NMR. The compound was screened for it’s antibacterial activity against Gram-positive and Gram-negative bacteria by the diffusion method on agar medium.